IMPACT OF STIMULATED MANDEL'SHTAM-BRILLOUIN SCATTERING ON THE RECEIVE CHANNEL IN PASSIVE OPTICAL SYSTEMS - V. Y. Bunas; D. V. Glushchenko; V. N. Uryadov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An analysis of nonlinear distortion in passive optical networks (PON), due to stimulated Mandel'shtam - Brillouin scattering is performed. It is shown that starting with a pump power of the signal / noise ratio at the input of the receiver opposite direction decreases sharply, which leads to increased likelihood of errors.